DocWIPE: Data Wiping Tool Using Randomized 512-Gram - Mohd Borham, Nurul Atifah; Kamaruddin Malik Mohamad (Applied Information Technology And Computer Science, 2021)
Number of computer users grow from year to year. As more people depends on computer to store information, data privacy become a concern. Failure to delete data securely may lead to data breach. In this project, a data wiping tool has been developed to delete files securely. This tool is called DocWIPE. This project creates an alternative way for file sanitization. DocWIPE tool focus on overwrite data in the file using randomized 512-gram technique. This tool uses Random Walk method with Pseudorandom Number Generator (PRNG), along with 512-gram to ensure the data will not be retrieved.